The dimensions of the academic productivism phenomenon and its harmful effect on scientific activity - Guimaraes, Jose Augusto Chaves [UNESP]; Hilario, Carla Mara [UNESP]; Gracio, Maria Claudia Cabrini [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2024)
The evaluation processes of academic life, which are predominantly quantitative, have led researchers to distort their productivity, in many cases, through unethical attitudes, leading to the so-called academic productivism. In this sense, this article aims to examine the phenomenon of academic productivism, seeking to identify its dimensions in the context of authorship attribution, the configuration of publications, citations, and predatory publications, and discuss its effects on the scientific communication process. To do so, it uses a critical review of the literature, focusing on issues relating to the sociology of science and ethics in scientific production. The article highlights the need to consider elements of a qualitative nature when evaluating scientific productivity, reflecting an ethical commitment to scientific practice. It concludes that academic productivism has led to the practice of valuing publication as the ultimate objective of research and intellectual production, restricting investigative activity and the production of knowledge to a quantification of results.
Keywords: academic productivism; scientific assessment; scientific publication; research ethics